Berberine inhibits glioma cell migration and invasion by suppressing TGF-β1/COL11A1 pathway - Sun, Yuxue; Huang, Haiyan; Zhan, Zhixin; Gao, Haijun; Zhang, Chaochao; Lai, Jiacheng; Cao, Junguo; Li, Chaoyue; Chen, Yong; Liu, Ziqiang (Biochemical and biophysical research communications, 2022)
Glioma is a clinically heterogeneous disease with a poor prognosis. Berberine (BBR), as a multi-target anti-tumor alkaloid, has the ability to penetrate the blood-brain barrier and shows cytotoxicity to glioma cells. In previous studies, we demonstrated that berberine inhibits glioma cell proliferation by inhibiting mutant p53 protein and promoting mitochondrial damage. In addition, berberine has been shown to reduce collagen accumulation in pulmonary fibrosis, diabetic nephropathy and arthritis. However, its effect on collagen in cancer needs to be further elucidated. In this study, we proved that the collagen XI alpha 1 chain (COL11A1) is highly expressed in glioma cell lines and associated with migration and invasion of glioma cells. Knocking down COL11A1 caused decreased expression of MMPs. Berberine could inhibit the migration and invasion of glioma cells by suppressing the TGF-β1/COL11A1 pathway and changes actin cytoskeleton arrangement. Nude mouse subcutaneous xenografts model also showed that berberine inhibited the expression of COL11A1 in vivo. Collectively, berberine that targets COL11A1 to inhibit glioma migration and invasion, may serve as a promising candidate for the development of anti-glioma drugs in the future.
Gesehen am 17.02.2023